The Influence of Tax Audit and Tax Collection on The Receipt of Income Tax Article 25 For Corpotare Taxpayers At KPP Pratama Prabumulih - Alkahfi, Bayu Dharmaraga (Journal of Accounting and Finance Management, 2024)
This study aims to measure the impact of tax audits and tax collection on the income tax revenue under Article 25 for corporate taxpayers at KPP Pratama Prabumulih for the period 2019-2023. The sampling technique used was purposive sampling. The data analysis technique used is multiple linear regression analysis with the aid of SPSS 19. The results of this study indicate that tax audits do not have a significant effect on income tax revenue under Article 25 for corporate taxpayers, while tax collection has a positive and significant effect on income tax revenue under Article 25 for corporate taxpayers.